Why and How Stories Matter in Treating Children with T1DM—Best Practice from CDiC - Kalra, Sanjay; Shukla, Rishi; Chugh, Shuchy; Dinakaran, P. (Journal of Social Health and Diabetes, 2021)
Type 1 diabetes mellitus (T1DM) is a lifelong disorder that mostly happens any time during childhood. It needs constant care and attention. Self-management becomes very essential as there are multiple factors that influence management of blood glucose levels and good outcomes. Diabetes education1 is essential for this and it involves the process of providing the person with the knowledge and skills needed to perform diabetes self-care, manage crises, and to make lifestyle changes to successfully manage their life. It begins with teaching of survival skills and continues with higher learning to fit diabetes into lives of people with diabetes rather than changing the lives to manage diabetes. Although parents are responsible for this initially, children must be part of this learning and journey as they are the one who must deal with diabetes in their life.Although knowledge transfer from scientific (truth and fact based) and narrative story (experience and meaning based) is fundamentally different but narrative or stories are better absorbed and retained. Storytelling and experience sharing are rapidly developing fields in medical education, but its potential has yet to be realized in medical education. The Changing Diabetes in Children program focused at reaching out to the economically underprivileged children with T1DM has implemented the use of stories to help the T1DM child learn to take insulin injections and understand the basic do’s and don’t’s for proper diabetes management and motivate them to become self-reliant and independent adults in long run.
Keywords: type 1 diabetes mellitus; diabetes education stories; motivation; good habits